INVESTIGATION OF THE ANTIOXIDANT PROPERTIES OF SPENT COFFEE GROUNDS EXTRACTS - Milić, Anita; Tepić Horecki, Aleksandra; Škaljac, Snežana; Šumić, Zdravko; Cvetković, Biljana; Pavlić, Branimir; Jokanović, Marija (Food and Feed Research, 2024)
Coffee is one of the most consumed beverages worldwide. During coffee processing, a significant amount of by-products is generated, with coffee grounds being the primary by-product resulting from both beverage preparation and instant coffee production. The yield of bioactive compounds extracted from coffee grounds depends on the type of coffee, growing and processing conditions. The antioxidant activity of coffee grounds is mainly attributed to their high phenolic content.The main goal of this study was to investigate the antioxidant activity of dried coffee grounds remaining in the machine after espresso preparation, with a focus on determining the total phenolic content, flavonoids and antioxidant activity through FRAP, DPPH and ABTS tests. Four solvents were used for the extraction and isolation of antioxidant components: 70% ethanol, distilled water and mixtures of 70% ethanol:water in different ratios (70% water and 30% ethanol, and 30% water and 70% ethanol).Based on the research results, it was concluded that the solvents of ethanol and its mixtures with water presents better solution for maximizing the contents of phenols and flavonoids, as well as for achieving the highest antioxidant activity in spent coffee grounds extracts. The results of this research also suggest that coffee waste could be used as a significant source of bioactive compounds, provided that appropriate extraction solvents are used.